Modeling of Inverter Fed Five Phase Induction Motor using V/f Control Technique (International Journal of Current Engineering and Technology, 2015)
Multiphase Variable-speed motor drivers have substantially grown with the advancement in power electronics in thebeginning of this century. Reference frame theory concept is used for analysis & performance of five phase inductionmachine. Traditionally three phase supply is produced and therefore Multiphase inverter is used to providemultiphase supply for multiphase supply. Simulation model of five phase induction machine in dqxyo axis based onmathematical modeling & it’s controlling using V/f Control Technique is modeled using simpower system block-set ofMatlab/simulink. Spwm Technique is used to generate the pulses for the inverter.
Keywords: Inverter; Spwm Technique; Five phase Induction Motor; V/f Control.